Laminate, fireproof panel, and manufacturing method of laminate

By bonding a geopolymer foam with specific properties to a metal body, the laminate addresses the issue of component separation at high temperatures, providing improved fire resistance and thermal insulation.

JP2024178032APending Publication Date: 2024-12-24JSP CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023096520
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing laminates using metal and inorganic materials suffer from poor fire resistance due to separation of components at high temperatures, such as cellular concrete panels and adhesive-based fire-resistant panels.

Method used

A laminate is created by adhering a geopolymer foam with a density between 100 kg/m³ and 600 kg/m³ to a metal body, where the bonded area ratio is 50% or more, using a geopolymer foam made from a reaction product of aluminosilicate and alkali metal silicate, with specific molar ratios and additives to enhance adhesion and fire resistance.

Benefits of technology

The laminate achieves excellent adhesion and improved fire resistance, suitable for use as a fireproof panel with enhanced thermal insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178032000001_ABST
    Figure 2024178032000001_ABST
Patent Text Reader

Abstract

To provide a laminate having excellent adhesiveness between a geopolymer foam portion and a metal body and good fireproof property.SOLUTION: In a laminate obtained by bonding a metal body and a geopolymer foam, a density of the geopolymer foam is 100 kg / m3 or over and 600 kg / m3 or under, and an area ratio of an area where the metal body and the geopolymer foam are bonded to each other is 50% or over in a portion where the geopolymer foam out of the metal body is laminated.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the art of laminates, fire-resistant panels and methods of manufacturing laminates. [Background technology]

[0002] Composite materials of metals and inorganic materials have been known for some time. Such composite materials are used, for example, as building materials such as walls and floors of buildings, and as components of vehicles, etc. When using composite materials as building materials, components of vehicles, etc., sufficient fire resistance may also be required.

[0003] For example, Patent Document 1 discloses an aerated concrete composite panel in which metal plates and mortar are laminated. Specifically, in the technology of Patent Document 1, mortar is injected into a metal frame in which reinforcing steel bars are installed, and high-temperature, high-pressure steam curing is performed to integrate the metal frame and the mortar, thereby obtaining an aerated concrete composite panel.

[0004] Patent Document 2 discloses a heat insulating fireproof panel in which a metal plate and a core material made of inorganic fiber material and inorganic material are laminated together. In Patent Document 2, the metal plate and the core material are laminated together via an adhesive layer made of an adhesive. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 60-010041 [Patent Document 2] JP 2014-134071 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the aerated concrete composite member of Patent Document 1 had a problem in that the aerated concrete collapsed when heated at high temperatures, causing the metal plate and the aerated concrete to peel off. Similarly, the heat-resistant and fire-resistant panel of Patent Document 2 also used an adhesive, and so when heated at high temperatures, the metal material and the core material sometimes peeled off. As described above, the techniques of Patent Documents 1 and 2 left room for improvement in terms of fire resistance. In consideration of the above circumstances, the present invention aims to improve the fire resistance of a laminate of a metal plate and an inorganic foam. [Means for solving the problem]

[0007] [1] A laminate in which a metal body and a geopolymer foam are bonded together, and the density of the geopolymer foam is 100 kg / m 3 More than 600kg / m 3 The laminate is as follows: wherein the area ratio of the region where the metal body and the geopolymer foam are adhered to each other in the portion of the metal body where the geopolymer foam is laminated is 50% or more.

[0008] [2] The laminate described in [1], wherein the geopolymer foam comprises a reaction product of an aluminosilicate and an alkali metal silicate, and an aggregate.

[0009] [3] The laminate described in [2], wherein the molar ratio of Ca element to the sum of Al element and Si element in the geopolymer foam is 0.4 or less.

[0010] [4] A fire-resistant panel comprising a laminate according to any one of [1] to [3].

[0011] [5] A method for producing a laminate of a geopolymer foam and a metal body, comprising: introducing a foamable composition slurry containing an aluminosilicate, an alkali metal silicate, aggregate, water, and a foaming agent into a mold in which the metal body is disposed or into a mold in which the metal body constitutes at least a part of the mold surface; and foaming the foamable composition slurry to a density of 100 kg / m. 3 More than 600kg / m 3A method for manufacturing a laminate, comprising the steps of forming a geopolymer foam and adhering the metal body and the geopolymer foam. Effect of the Invention

[0012] The laminate of the present invention has excellent adhesion between the geopolymer foam and the metal body, and has good fire resistance. According to the manufacturing method of the present invention, it is possible to obtain a laminate having good fire resistance by bonding the geopolymer foam and the metal body well. In addition, the laminate of the present invention can be used as a fire-resistant panel. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a cross-sectional view of an example of a laminate according to the embodiment. [Diagram 2] FIG. 4 is an explanatory view showing an example of a manufacturing method (third step) according to the embodiment. [Diagram 3] 1 is a photograph of an example of a laminate according to an embodiment. [Figure 4] 13 is an example of an image used to calculate the area ratio of an adhesive region in a laminated portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] [Laminate] Figure 1 is an example of a cross-sectional view of a laminate according to the present invention. As illustrated in Figure 1, the laminate according to the present invention is a structure in which a metal body and a geopolymer foam are bonded and laminated. In the laminate, the geopolymer foam is directly bonded to the metal body without using an adhesive. The manufacturing method of the laminate will be described later.

[0015] Geopolymer foam is a geopolymer with many bubbles, and the geopolymer is a reaction product of aluminosilicate and alkali metal silicate. Specifically, the geopolymer is an inorganic polymer with a tetrahedral structure formed from SiO4 and AlO4, and has a structure in which cations that compensate for the negative charge of AlO4 are contained in the network of the tetrahedral structure. Since the geopolymer foam has many bubbles, it also has excellent thermal insulation properties.

[0016] Specifically, the geopolymer foam comprises a reaction product of an aluminosilicate and an alkali metal silicate (i.e., a geopolymer) and an aggregate.

[0017] <Aluminosilicate> Aluminosilicates (xM2O·yAl2O3·zSiO2·nH2O, where M is an alkali metal) are compounds in which some of the silicon atoms in silicates are replaced by aluminum atoms.

[0018] The SiO2 (silicon dioxide) content in the aluminosilicate is preferably 20% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 70% by mass or less. When the SiO2 content in the aluminosilicate is in this range, the geopolymer foam is likely to form a good cell structure with a large number of bubbles.

[0019] The content of Al2O3 in the aluminosilicate is preferably 20% by mass or more and 70% by mass or less, and more preferably 30% by mass or more and 50% by mass or less, based on the total mass of the aluminosilicate (100% by mass). When the content of Al2O3 is in this range, it is easy to improve the compressive strength of the geopolymer foam.

[0020] The SiO2 content and Al2O3 content in the aluminosilicate can be determined by quantifying each element using an X-ray fluorescence analyzer (for example, EA6000V manufactured by Hitachi High-Tech Science) or the like.

[0021] Specifically, examples of the aluminosilicate include clay minerals such as beidellite, bentonite, metakaolin, kaolinite, halloysite, montmorillonite, pyrophyllite, vermiculite, mica, chlorite, saponite, sepiolite, and acid clay; industrial wastes such as fly ash, red mud, silica fume, blast furnace slag, rice husk, and sewage sludge incineration ash; natural aluminosilicate minerals and their calcined products (e.g., metakaolin: Al2O3·2SiO2), volcanic ash, and other silicate minerals containing aluminum, and one or more of these may be used in combination. When two or more aluminosilicates are used in combination, it is preferable to mix them so that the SiO2 content and the Al2O3 content satisfy the above range. Among these, metakaolin is preferable as the aluminosilicate. By appropriately grinding and classifying these substances and using a specific fraction, it is possible to adjust the aluminosilicate to a desired composition.

[0022] When metakaolin is used as the aluminosilicate, the ratio of metakaolin in the aluminosilicate is preferably 50% by mass or more. When the ratio of metakaolin in the aluminosilicate is within the above range, a good cell structure with a large number of bubbles is easily formed. From the above viewpoint, the ratio of metakaolin in the aluminosilicate is more preferably 60% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0023] The average particle size of the aluminosilicate is preferably 0.1 μm to 50 μm, more preferably 0.3 μm to 30 μm, and even more preferably 0.5 μm to 10 μm. When the average particle size of the aluminosilicate is within this range, the produced geopolymer foam has a good cellular structure. The average particle size means the diameter of a virtual sphere having the same volume as the particle.

[0024] The crystallinity of the aluminosilicate is preferably 20% or less, more preferably 10% or less. When the crystallinity of the aluminosilicate is in this range, when the aluminosilicate is reacted with an alkali metal silicate described later in an aqueous solution, aluminum ions are easily eluted from the aluminosilicate source by the alkali component derived from the alkali metal silicate, and silicic acid monomers are easily generated, and polycondensation is stably performed, so that a good cell structure is easily formed.

[0025] The degree of crystallinity can be determined based on the method (absolute method) described in JIS K0131-1996. For example, the degree of crystallinity can be measured by performing X-ray diffraction measurement on the powder of aluminosilicate at room temperature using an X-ray analyzer (e.g., SmartLab, manufactured by Rigaku Corporation) having a two-dimensional detector, setting the 2θ range to 10 to 40°. The degree of crystallinity can be determined by performing profile fitting on the diffraction pattern measured by X-ray diffraction measurement, and calculating the ratio of the peak area of ​​the crystalline component to the total peak area ([peak area of ​​the crystalline component] + [halo pattern area of ​​the amorphous component]) from the obtained X-ray diffraction.

[0026] <Alkali metal silicate> Examples of alkali metal silicates include potassium silicate, sodium silicate (water glass), and lithium silicate, and one or more of these can be used. Among these, the alkali metal silicate is preferably potassium silicate. The molar ratio of SiO2 to K2O (SiO2 / K2O ratio) in potassium silicate is preferably 1 to 5, more preferably 1.5 to 4.5, and even more preferably 3 to 4. By setting the molar ratio (SiO2 / K2O ratio) in the above range, the strength of the geopolymer foam can be further improved.

[0027] The geopolymer foam is based on the reaction product (i.e., geopolymer) of the above-mentioned aluminosilicate and alkali metal silicate. Specifically, the content of the geopolymer in the geopolymer foam is preferably 40% by mass or more, more preferably 50% or more, and even more preferably 60% or more.

[0028] <Aggregate> Examples of aggregates include one or more of mica, wollastonite, chalk, talc, molokite, cordierite, basalt, feldspar, zircon, graphite, and borax, among which mica is preferred. Mica is a silicate mineral generally called muscovite, and is KAl2(AlSiO 10 )(F,OH)2. In the present invention, the term "mica" includes sheet silicate (phyllosilicate) minerals that are physically and chemically similar. When the aggregate contains mica, the mica preferably has an average particle size of 50 μm or more and 200 μm or less from the viewpoint of forming a good air bubble structure.

[0029] The aggregate content in the geopolymer foam is preferably 5% by mass or more and 60% by mass or less, more preferably 10% by mass or more and 50% by mass or less, and even more preferably 20% by mass or more and 40% by mass or less.

[0030] The geopolymer foam may contain other components in addition to the geopolymer and aggregate. Examples of other components include a bubble-opening agent, reinforcing fibers, and a foam nucleating agent. The reinforcing fibers are contained for the purpose of improving the strength of the geopolymer foam and preventing cracks. Examples of reinforcing fibers include vinylon fibers, polypropylene fibers, aramid fibers, acrylic fibers, rayon fibers, carbon fibers, glass fibers, potassium titanate whiskers, alumina fibers, steel wool, and slag wool. The strength of the geopolymer foam can be increased by containing reinforcing fibers in the geopolymer foam. Examples of the bubble-opening agent include microorganisms such as yeast and algae, proteins, and surfactants. Examples of the foam nucleating agent include inorganic powders such as talc and calcium carbonate, and talc is more preferable.

[0031] The content of other components in the geopolymer foam is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. The content of the foam nucleating agent in the geopolymer foam is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0032] The density of the geopolymer foam of the present invention is 100 kg / m 3 More than 600kg / m 3 The density is below 120 kg / m. If the density of the geopolymer foam is too high, the geopolymer foam will shrink due to drying when curing the laminate after it is obtained, and the difference in the shrinkage rate between the metal body and the geopolymer foam may reduce the adhesiveness between the metal body and the geopolymer foam. From the viewpoint of weight reduction, it is also preferable that the density of the geopolymer foam is not too high. On the other hand, if the density of the geopolymer foam is too low, the strength of the bubble membrane part of the geopolymer foam may decrease, and adhesiveness may not be maintained. From the above viewpoints, the density of the geopolymer foam is set to 120 kg / m. 3 More than 500kg / m 3 It is preferable that the thickness is less than 160 kg / m 3 More than 400kg / m 3It is more preferable that:

[0033] In the geopolymer foam, the ratio of the number of moles of Ca element to the total number of moles of Al element and Si element (Ca / (Al+Si)) is preferably 0.4 or less, more preferably 0.2 or less, even more preferably 0.1 or less, particularly preferably 0.05 or less, and most preferably 0.01 or less. When the molar ratio (Ca / (Al+Si)) is in the above range, the fire resistance is improved. The lower limit of the molar ratio (Ca / (Al+Si)) is not particularly limited, but it is preferably about 0.001 or more, or Ca is not contained. (Ca / (Al+Si)) can be adjusted by changing the type and content of the aluminosilicate used, or by adjusting the type of additive. In addition, the molar ratio (Si / Al) in the geopolymer foam is preferably 0.5 to 5, more preferably 1 to 3.

[0034] The thickness of the geopolymer foam in the laminate (thickness in the lamination direction) can be changed appropriately depending on the application, but is expected to be, for example, 1 cm or more and 50 cm or less.

[0035] The average bubble diameter of the geopolymer foam in the laminate is preferably 0.1 mm to 4 mm. By setting the average bubble diameter within the above range, a bubble wall with excellent strength is formed and is less likely to crack when heated. From the above viewpoint, the average bubble diameter is more preferably 0.3 mm to 3 mm, and even more preferably 0.5 mm to 2 mm.

[0036] The metal body used in the laminate is not particularly limited, but for example, a plate-shaped metal body, a steel plate, an aluminum alloy plate, a stainless steel plate, etc. are used. Among these, a steel plate and an aluminum alloy plate are preferable. A metal body whose surface is plated may be used. When the metal body is plate-shaped, the thickness may be appropriately changed depending on the application, but is assumed to be, for example, 0.05 cm or more and 0.2 cm or less. The shape of the metal body is not limited to a plate shape, and may be appropriately changed depending on the application.

[0037] As described above, in the laminate of the present invention, the geopolymer foam is directly bonded to the metal body. In the following description, the part of the metal body where the geopolymer foam is laminated is referred to as the "laminated part". As illustrated in FIG. 1, the laminated part is a part where the metal body and the geopolymer foam are arranged facing each other, and it does not matter whether the metal body and the geopolymer foam are in direct contact with each other. Note that the area on the surface of the metal body where the geopolymer foam is not formed (the area where the geopolymer foam is not laminated) is not included in the laminated part. Therefore, when the geopolymer foam is laminated on a part of the surface of the metal body, the laminated part is the area A, and the area where the foam is not formed other than the area A is not included in the laminated part.

[0038] The adhesive strength between the metal body and the geopolymer foam is preferably 3N / cm 2 More preferably, 5N / cm 2 More preferably, it is 10 N / cm 2 The upper limit of the adhesive strength is not particularly set, but the upper limit of the adhesive strength is that the geopolymer foam itself has an adhesive strength that causes material destruction in the adhesive strength test.

[0039] The adhesive strength between the metal body and the geopolymer foam can be determined as follows. First, a sample of a given size (for example, 5 x 5 cm) is obtained by cutting the laminate along the lamination direction. Then, a metal tensile test jig is fixed with adhesive to the surface of the geopolymer foam opposite the metal body and the surface of the metal body opposite the geopolymer foam, and a peel test is performed to confirm the adhesive strength. The peel test is performed using a tabletop testing machine (autograph) with a test speed of 2 mm / min, applying a tensile load perpendicular to the interface of the laminate, based on the JIS K6849-1994 adhesive tensile adhesive strength test method, until the geopolymer foam is destroyed or until interfacial peeling occurs at the interface between the metal and the geopolymer foam.

[0040] In the present invention, in the laminated portion of the metal body and the geopolymer foam, the area ratio of the region where the metal body and the geopolymer foam are bonded (hereinafter referred to as the "bonded area") is 50% or more. The area ratio of the bonded area in the laminated portion is a value measured as follows.

[0041] First, the laminated portion of the laminate is cut out to obtain a sample of a predetermined size (for example, 5 x 5 cm). Next, the geopolymer foam portion of the sample is scraped off until the thickness of the geopolymer foam is 0.01 mm or more and 0.1 mm or less. That is, the geopolymer foam is scraped off so that the height of the geopolymer foam in the laminated portion of the metal body is 0.01 mm or more and 0.1 mm or less. Then, the surface of the sample after scraping off the geopolymer foam is subjected to image analysis to measure the area of ​​the geopolymer portion of the geopolymer foam remaining in the laminated portion of the metal body. Specifically, the image of the sample captured with an imaging device (OLYMPUS STYLUS TG-4 Tough manufactured by Olympus) so that the entire area of ​​the surface of the sample is included is analyzed with a known image analysis software (for example, Winroof2021: manufactured by Mitani Shoji). The captured image is converted to a monochrome image (8 bit). Next, the monochrome image is binarized using a mode method, so that the portion representing the geopolymer foam (i.e., the portion where the geopolymer foam remains) and the portion representing the metal body (i.e., the portion where the surface of the metal body is exposed) can be distinguished. In the binarized image, for example, the portion representing the geopolymer foam is displayed in white, and the portion representing the metal body is displayed in a color other than white. Then, the area of ​​the portion representing the geopolymer foam in the image is calculated, and the area ratio of the adhesive region in the laminated portion of the metal body is calculated.

[0042] If the surface area ratio of the adhesive region in the laminated portion is 50% or more, it is possible to suppress the geopolymer foam from detaching from the metal body. From the above viewpoint, the surface area ratio of the adhesive region in the laminated portion is preferably 70% or more, more preferably 80% or more.

[0043] The shape of the laminate of the present invention is not particularly limited as long as it includes a laminated portion and the area ratio of the adhesive region in the laminated portion is 50% or more. Therefore, for example, the laminate may be a container-shaped laminate in which the metal body includes a bottom and a side wall, and the geopolymer foam is located inside the bottom and the side wall. In such a laminate, it is preferable that the area ratio of the adhesive region in the laminated portion with the geopolymer foam in the bottom or side wall, excluding the bent portion, is 50% or more. If the sample does not have a flat portion, it is preferable to select and measure a gently sloping flat portion of the sample, excluding the bent portion, etc. In this case, the area of ​​the adhesive region is calculated as a ratio of the projected area.

[0044] The laminate of the present invention is suitable for use as a fire-resistant panel for buildings and vehicles (for example, underfloor surfaces) such as railways. In addition, since the laminate of the present invention contains a geopolymer foam, its cellular structure gives it excellent heat resistance, and it can also be used as a heat-resistant panel.

[0045] [Method of manufacturing laminate] An example of a method for producing the laminate described above will be described. The production method of the present invention includes the following first, second and third steps. 3 More than 600kg / m 3 The following geopolymer foam laminates bonded to metal bodies are produced:

[0046] First step: obtaining a reaction slurry containing an aluminosilicate, an alkali metal silicate, an aggregate and water. The second step is a step of obtaining a foamable composition slurry by adding a foaming agent to the reaction slurry. The third step is forming a geopolymer foam from the foamable composition slurry and adhering the geopolymer foam directly to the metal body.

[0047] The first to third steps will be described in detail below.

[0048] <1st process> Specifically, in the first step, a mixture containing an aluminosilicate and aggregate (hereinafter referred to as the "raw material mixture") is mixed with an aqueous alkali metal silicate solution, and water for viscosity adjustment as necessary, to obtain a reaction slurry. In the reaction slurry, the aluminosilicate reacts with the alkali metal silicate to form a geopolymer.

[0049] As the aluminosilicate contained in the reaction slurry, in addition to the various aluminosilicates exemplified for the laminate, one containing the aluminosilicate as a component is used.

[0050] When aluminosilicate reacts with alkali metal silicate, it dissolves aluminum ions into the aqueous solution in the reaction slurry and produces silicic acid monomers (silicic acid, Si(OH)4). The silicic acid monomers thus produced undergo polycondensation with the cations present in the reaction slurry to form a geopolymer with a polymer network of SiO4·AlO4 tetrahedral structure.

[0051] The alkali metal silicate contained in the reaction slurry may be any of the various alkali metal silicates exemplified for the laminate, as well as a compound containing the alkali metal silicate as a component. When an alkali metal silicate is dissolved in water to prepare an aqueous alkali metal silicate solution, the aqueous solution becomes highly alkaline, and the reaction slurry becomes highly alkaline.

[0052] In the reaction slurry, the alkali metal silicate in the alkali metal silicate aqueous solution reacts with the aluminosilicate, dissolving cations such as Al from the aluminosilicate into the reaction slurry. Also, silicic acid monomers are present in the reaction slurry. Therefore, the alkali metal silicate becomes a source of silicic acid monomers that form geopolymers by polycondensation.

[0053] The alkali metal silicate is preferably added as an aqueous solution of alkali metal silicate to prepare a reaction slurry. For example, the concentration of the alkali metal silicate in the aqueous solution of alkali metal silicate is preferably 20% by mass or more and 60% by mass or less, more preferably 22% by mass or more and 50% by mass or less, and even more preferably 25% by mass or more and 45% by mass or less. When the concentration of the alkali metal silicate is within the above range, the foam moldability of the reaction slurry in which the aluminosilicate and the aqueous solution of alkali metal silicate are mixed can be improved. However, if the reaction between the alkali metal silicate and the aluminosilicate occurs, it is not essential to use the alkali metal silicate as the aqueous solution of alkali metal silicate.

[0054] In order to adjust the pH of the reaction slurry to be alkaline and promote the reaction between the aluminosilicate and the alkali metal silicate, an alkali metal hydroxide such as potassium hydroxide or sodium hydroxide can be added. In particular, it is preferable to add potassium hydroxide to the reaction slurry. The amount of potassium hydroxide added is preferably 10 parts by mass or more and 90 parts by mass or less, more preferably 50 parts by mass or more and 80 parts by mass or less, based on 100 parts by mass of the alkali metal silicate.

[0055] The amount of the alkali metal silicate added is preferably 20 parts by mass or more and 200 parts by mass or less, more preferably 40 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of the SiO2 component in the aluminosilicate, from the viewpoint of forming a good geopolymer and uniformly dispersing each component in the foamable composition slurry. It is preferable to add an aqueous solution of the alkali metal silicate so that the amount of the alkali metal silicate added is within the above range.

[0056] From the viewpoint of improving fire resistance, the aluminosilicate and alkali metal silicate are added so that the molar ratio (Ca / (Al+Si)) in the reaction slurry is preferably 0.4 or less, more preferably 0.2 or less, even more preferably 0.1 or less, particularly preferably 0.05 or less, and most preferably 0.01 or less. Note that the aluminosilicate and alkali metal silicate may contain calcium as an impurity or accessory component. The molar ratio (Si / Al) in the reaction slurry is preferably 0.5 or more and 5 or less, more preferably 1 or more and 3 or less.

[0057] As the aggregate contained in the reaction slurry, various aggregates exemplified for the laminate are used. The amount of aggregate added is preferably 100 parts by mass or more and 500 parts by mass or less with respect to 100 parts by mass of the SiO2 component in the aluminosilicate. If the amount of aggregate added is too small, the geopolymer foam is more likely to crack. On the other hand, if the amount of aggregate added is too large, there is a problem that the compressive strength of the geopolymer foam is reduced. If the amount of aggregate added is within the above range, the compressive strength can be improved while suppressing the occurrence of cracks in the geopolymer foam. From the above viewpoint, the amount of aggregate added is more preferably 150 parts by mass or more and 400 parts by mass or less, and even more preferably 180 parts by mass or more and 300 parts by mass or less with respect to 100 parts by mass of the SiO2 component in the aluminosilicate.

[0058] The aluminosilicate, alkali metal silicate and aggregate may contain other components. In this case, the amount of the aluminosilicate, alkali metal silicate and aggregate is calculated as the amount of the active ingredient excluding the other ingredients for each of the aluminosilicate, alkali metal silicate and aggregate. The content of the SiO2 component in the aluminosilicate or alkali metal silicate can be determined by, for example, composition analysis using X-rays or the like to determine the ratio of the SiO2 component present.

[0059] In the first step, various other additives may be added to the raw material mixture of the aluminosilicate and the aggregate. As the other additives, various components exemplified for the laminate are used. When a foaming nucleating agent is added as the other component, the amount is preferably 1 part by mass or more and 40 parts by mass or less relative to 100 parts by mass of the SiO2 component in the aluminosilicate.

[0060] The amount of the other additives added is not particularly limited as long as the object of the present invention can be achieved, and is preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of the total of the aluminosilicate, alkali metal silicate, and aggregate.

[0061] The amount of water added to adjust the viscosity of the reaction slurry is not particularly limited, but is preferably 20% by mass or more and 50% by mass or less, and more preferably 25% by mass or more and 45% by mass or less, based on 100% by mass of the foamable composition slurry obtained in the second step described below. Water may be added independently, or may be added as a solvent when water glass is used as the alkali metal silicate.

[0062] The viscosity of the reaction slurry obtained in the first step is preferably 100 Pa s or less when measured at a spindle rotation speed of 6 rpm, and more preferably 1 Pa s to 15 Pa s when measured at 60 rpm. When the viscosity of the reaction slurry is within the above range, a sudden increase in viscosity due to the application of shear force to the reaction slurry in which the aggregate is dispersed does not occur, and air bubbles are easily formed.

[0063] The viscosity of the reaction slurry is measured using a viscometer (e.g., ATAGO VISCO manufactured by Atago Co., Ltd., equipped with an A3 spindle). The viscosity is measured immediately after mixing (before heating) the raw material mixture containing the aluminosilicate and aggregate with the aqueous alkali metal silicate solution (or the alkali metal silicate and water).

[0064] The reaction slurry obtained in the first step means a fluid in which solid components are dispersed or partially dissolved in water. The solid components include particles of the raw material mixture, aggregates, and particles such as geopolymers generated by the reaction of aluminosilicates and alkali metal silicates. In the reaction slurry, it is not necessary for the aluminosilicates and alkali metal silicates to completely react to form a geopolymer, and it is sufficient that the geopolymer formed from the aluminosilicates and alkali metal silicates exists as part of the reaction slurry. The proportion of solid components in the reaction slurry is preferably 30% to 90%, more preferably 50% to 80%. The medium of the reaction slurry is mainly composed of water, but water-soluble alcohols and the like may be added as secondary components.

[0065] The mixing method in the first step is not particularly limited, and for example, the materials are mixed at room temperature (25° C.) using a known mixer (e.g., a mortar mixer, a tilting mixer, a truck mixer, a two-shaft mixer, an omni mixer, a pan mixer, a planetary mixer, an Eirich mixer, etc.). The order in which the materials are added to the mixer, etc. is not particularly limited.

[0066] <Second process> In the second step, as described above, a foaming agent is added to the reaction slurry obtained in the first step to obtain a foamable composition slurry. Examples of the foaming agent include hydrogen peroxide, sodium peroxide, potassium peroxide, sodium perborate, and non-ferrous metal powder. Examples of the non-ferrous metal powder include aluminum powder. Among these, it is preferable to use at least one of hydrogen peroxide and non-ferrous metal powder, and it is more preferable to use hydrogen peroxide.

[0067] When hydrogen peroxide is used as a foaming agent, it is preferable to use it as hydrogen peroxide water. In this case, the concentration of hydrogen peroxide in the hydrogen peroxide water is preferably 10% by mass or more and 50% by mass or less. When the concentration of hydrogen peroxide in the hydrogen peroxide water is within the above range, the foamable composition slurry can be stably foamed, and an inorganic foam having a good cell structure can be easily obtained. From the above viewpoints, the concentration of hydrogen peroxide in the hydrogen peroxide water is more preferably 20% by mass or more and 40% by mass or less.

[0068] The amount of the foaming agent added can be appropriately set according to the design of the geopolymer foam to be produced, and is not particularly limited. The amount of the foaming agent added is preferably 0.5 parts by mass or more and 100 parts by mass or less, more preferably 1 part by mass or more and 50 parts by mass or less, and even more preferably 2 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the SiO2 component in the aluminosilicate. When hydrogen peroxide is used as a foaming agent, the amount of hydrogen peroxide added is preferably 0.5 parts by mass or more and 200 parts by mass or less, more preferably 1 part by mass or more and 150 parts by mass or less, and even more preferably 2 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the SiO2 component in the aluminosilicate. By adding the foaming agent within the above range, the foamable composition slurry is sufficiently foamed, and a geopolymer foam having excellent thermal insulation can be stably obtained. In addition, in the foamable composition slurry, it is not necessary for the aluminosilicate and the alkali metal silicate to completely react to form a geopolymer, and it is sufficient that a geopolymer formed from the aluminosilicate and the alkali metal silicate exists as a part of the reaction slurry.

[0069] <3rd process> Specifically, in the third step, the foamable composition slurry is introduced into a mold in which a metal body is disposed or into a mold in which a metal body constitutes at least a part of a mold surface, and then the foamable composition slurry is foamed to a density of 100 kg / m 3 More than 600kg / m 3The following geopolymer foam is formed to directly bond the metal body and the geopolymer foam. In the third step, it is not necessary to foam after the geopolymer is formed, and the aluminosilicate and the alkali metal silicate may react in parallel in the foaming stage to form the geopolymer and become a foam.

[0070] Fig. 2 is an explanatory diagram for explaining an example of the third step. Fig. 2 shows a U-shaped metal body (having a bottom and two side walls facing each other). However, the shape of the metal body may be changed as appropriate depending on the application.

[0071] First, in the third step, the foamable composition slurry obtained in the second step is introduced into the metal body mold. The shape of the mold is appropriately changed according to the shape of the desired laminate, and is not particularly limited as long as the metal body can be placed inside or a part of the mold doubles as a metal body and the geopolymer foam can be prevented from leaking. Note that FIG. 2 illustrates an example in which the metal body functions as a part of the mold surface (the bottom of the mold). However, it is also assumed that the metal body itself functions as the entire mold. When the metal body functions as the entire mold, a mold separate from the metal body is not essential.

[0072] After the foamable composition slurry is introduced into the mold, the foamable composition slurry is foamed by heating or the like to form a large number of bubbles in the geopolymer, and then solidified to obtain a geopolymer foam having a large number of bubbles.

[0073] When the foamable composition slurry is foamed, the geopolymer is pressed against the metal body by the foaming pressure, which increases the contact area between the geopolymer foam and the metal body, creating a state close to surface adhesion, which is thought to improve adhesion between the metal body and the geopolymer foam.

[0074] In the third step, the foamable composition slurry can be molded into a geopolymer foam of a desired shape by various molding methods. For example, the foamable composition slurry is poured into a mold to be molded, or the foamable composition slurry is pressed in a mold to suck out the water and dehydrate it to mold it, thereby molding the geopolymer foam into a desired shape.

[0075] The conditions for foaming the foamable composition slurry are appropriately set according to the desired physical properties of the geopolymer foam. For example, when foaming the foamable composition slurry by the casting method, the foamable composition slurry is reacted and foamed in a mold at a temperature of 20 to 100°C (preferably 50 to 80°C) and for a holding time of 30 minutes to 24 hours, to obtain a geopolymer foam.

[0076] When the casting method is used, the bubbles formed by foaming the foamable composition slurry in the third step grow and become larger within 30 minutes to 1 hour after the addition of the foaming agent. Note that geopolymer foams usually have mesopores derived from the geopolymer structure, but these mesopores are to be distinguished from the numerous bubbles formed by the foaming agent.

[0077] In the manufacturing method of the present invention, unlike physical foaming in which bubbles are formed by stirring, etc., the bubbles are gradually grown by adding a foaming agent, so the bubbles are less likely to become finer and there is less unevenness in the bubble diameter. It is easy to obtain a geopolymer foam with a uniform bubble structure.

[0078] The method for producing a geopolymer foam may include other steps in addition to the first, second, and third steps. For example, the method may include a step of firing the geopolymer foam obtained by the molding step. The fired geopolymer foam can prevent dimensional changes at high temperatures. EXAMPLES

[0079] The present invention will be described in detail with reference to examples, but the present invention is not limited to the examples.

[0080] The laminate was manufactured according to the composition shown in Table 1. The details of the raw materials of the geopolymer foam in the laminate are as follows. The metal body used in the laminate is a plate of SS400 (steel) with a thickness of 1 mm, as shown in Table 1.

[0081] [Aluminosilicate] Metakaolin (Hyogo Clay: HC-K-1300W, aluminosilicate content 99% by mass) Fly ash (Nippon Paper Industries: CfFA, aluminosilicate content 69% by mass, calcium oxide content less than 1% by mass) Blast furnace slag (manufactured by Nippon Paper Industries Co., Ltd.: no gypsum dihydrate added, aluminosilicate content 49% by mass, calcium oxide content 42% by mass) [Alkali metal silicates] Potassium silicate (Nihon Kagaku Kogyo: 2K potassium silicate) [Foam nucleating agent] Talc (Matsumura Sangyo: Hi-filler5000PJS) [aggregate] Mica (Seishin Enterprises: C100M) [Foaming agent] Hydrogen peroxide solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: hydrogen peroxide concentration 30% by mass)

[0082] Examples 1 to 5 and Comparative Examples 1 and 2 were produced as follows.

[0083] First, a raw material mixture was prepared by mixing aluminosilicate (metakaolin, fly ash, blast furnace slag), foaming nucleating agent, and aggregate in the ratio shown in Table 1. In Table 1, the amounts of aluminosilicate, foaming nucleating agent, alkali metal silicate, aggregate, and foaming agent added are values ​​based on 100 parts by mass of SiO2 component in the aluminosilicate. As raw materials, an alkali metal silicate aqueous solution and hydrogen peroxide solution were used, and the amounts added were the amounts of alkali metal silicate and hydrogen peroxide added converted into concentrations. In addition, an alkali metal silicate aqueous solution (concentration 37%, pH = 14) was prepared by mixing potassium silicate, potassium hydroxide, and distilled water.

[0084] Next, the raw material mixture and an aqueous alkali metal silicate solution were mixed so that the alkali metal silicate components were in the ratio shown in Table 1, distilled water was added as necessary, and the mixture was stirred at a stirring speed of 60 rpm to prepare a reaction slurry with a viscosity of 1 to 15 Pa s at a spindle rotation speed of 60 rpm. Next, a foaming agent was added to the reaction slurry in the ratio shown in Table 1, and the mixture was stirred with a stirring spatula at a stirring speed of 60 rpm for 1 minute to prepare a foamable composition slurry.

[0085] A mold in which a plate-shaped metal body was placed was prepared. The metal body was a U-shaped metal body having a bottom with inner dimensions of 30 cm x 30 cm and a side wall with a height of 3 cm. The mold was used in a shape that allowed the metal body to be placed inside, as shown in the example of FIG. 2. The foamable composition slurry was introduced into the mold to contact the metal body. Next, the mold was sealed and kept in an oven at a temperature of 60°C for 1 hour to react and foam the foamable composition slurry, thereby obtaining a laminate in which the metal body and the geopolymer foam were directly bonded. The surface of the geopolymer foam in the laminate was cut so that the thickness was 30 mm. At this time, the pressure inside the mold was atmospheric pressure, and foaming was completed in about 30 minutes, and solidification was completed in about 1 hour. Thereafter, the laminate from which the mold was removed was further kept at 60°C for about 1 day to dry. FIG. 3 is a photograph of an example of a laminate according to the embodiment.

[0086] In Comparative Example 3, a laminate was obtained by adhering a geopolymer foam to a metal body using an adhesive (100% silylated urethane resin). Specifically, after preparing a reaction slurry with the composition shown in Table 1, a foaming agent was added to prepare a foamable composition slurry. The foamable composition slurry was introduced into a 40 cm x 40 cm x 5 cm mold, and the foamable composition slurry was foamed and molded to obtain a geopolymer foam. The preparation of the reaction slurry and the foamable composition slurry, and the manufacturing conditions for the geopolymer foam were the same as those in Examples 1 to 5 and Comparative Examples 1 and 2. Then, the geopolymer foam cut into a size of 30 cm x 30 cm x 3 cm was adhered to a metal body (30 cm x 30 cm) with an adhesive.

[0087] In Comparative Example 4, lightweight aerated concrete (ALC) was used instead of the geopolymer foam, and was bonded to a metal body with an adhesive (100% silylated urethane resin) in the same manner as in Comparative Example 3 to obtain a laminate. A commercially available ALC panel (general flat panel, 600 x 1800 mm, thickness 50 mm) was used as the lightweight aerated concrete. Then, the lightweight aerated concrete cut to 30 cm x 30 cm was bonded to a metal body (30 cm x 30 cm) with an adhesive.

[0088] The obtained laminate was evaluated for the following items as follows. The size of the obtained laminate was 30 cm wide, 30 cm high, and 3 cm thick. In addition, in the laminates of Examples 1 to 5, the content of geopolymer in the geopolymer foam was 40 mass% or more, taking into account the blending amount of aluminosilicate and alkali metal silicate.

[0089] [Table 1]

[0090] [density] The density of the geopolymer foam was determined by dividing the weight of the geopolymer foam by the outer diameter dimension of the geopolymer foam.

[0091] [Adhesive strength] The adhesive strength between the metal body and the geopolymer foam was measured as follows. First, a sample of 5 x 5 cm size was obtained by cutting the laminate along the lamination direction. Then, a metal tensile test jig was fixed with adhesive to the opposite side of the geopolymer foam from the metal body and the opposite side of the metal body from the geopolymer foam, and a peel test was performed to confirm the adhesive strength. The peel test was performed using a tabletop tester (autograph) with a test speed of 2 mm / min, applying a tensile load perpendicular to the interface of the laminate, based on the JIS K6849-1994 adhesive tensile adhesive strength test method. The test was performed until the geopolymer foam was destroyed or the interface peeled off.

[0092] [Adhesion rate] The area ratio of the adhesive region in the laminated portion of the metal body was measured by the following method. For the sample after the tensile test described above, the geopolymer foam was scraped toward the metal body until the thickness of the geopolymer foam was 0.01 mm or more and 0.1 mm or less. Then, the surface of the sample after scraping the geopolymer foam was analyzed by image analysis to measure the area of ​​the geopolymer portion of the geopolymer foam remaining in the laminated portion of the metal body. Specifically, the image of the sample taken with an imaging device (OLYMPUS STYLUS TG-4 Tough made by Olympus) so that the entire area of ​​the surface of the sample was included was analyzed with image analysis software (for example, Winroof2021: made by Mitani Shoji). The captured image was converted into a monochrome image (8 bit). Next, the monochrome image was binarized by the mode method to distinguish the part representing the geopolymer foam (i.e. the part where the geopolymer foam remains) from the part representing the metal body (the part where the metal body is exposed) by color. Figure 4 is an example of an image after binarization. In Figure 4, the lighter colored parts represent the geopolymer foam, and the darker colored parts represent the metal body. The area of ​​the part in the image that represents the geopolymer foam was then calculated, and the area ratio of the adhesive region in the layered part of the metal body was calculated to obtain the adhesion rate.

[0093] [Fire resistance] The fire resistance of the laminate was evaluated by conducting a fire resistance test. For the fire resistance test, two laminates measuring 30cm x 30cm x 3cm were placed in a heating furnace. The laminate was placed so that the metal body side was facing the furnace. Next, the temperature inside the furnace was raised (up to 1 hour) under the heating conditions described in JIS A 1304, and the laminate was heated from the metal body side. The change in temperature of the surface of the laminate (the surface on the geopolymer foam side) was measured every 30 seconds. The surface temperature was measured at two points on each laminate. Then, the state of cracking after 1 hour and the surface temperature after 1 hour (the temperature of the surface of the geopolymer foam) were confirmed. The surface temperature was the average value of the two points.

[0094] The cracking after one hour was evaluated according to the following criteria. ○: The shape of the geopolymer foam was maintained. △: Slight cracks occurred in the geopolymer foam. ×: Cracks occurred in the geopolymer foam and the geopolymer foam fell off from the metal body.

[0095] In addition, in Comparative Examples 2 to 4, the geopolymer foam fell off from the metal body, so it was impossible to measure the surface temperature.

[0096] [Average bubble diameter] The method for determining the average bubble diameter of geopolymers is as follows. Specifically, image data of the cross section of the test piece is obtained at a magnification of 20 times using a measuring device (Keyence Corporation Digital Microscope VHX-7000). In this image data, the area of ​​each bubble is measured using Nano Systems Corporation's image processing software NS2K-pro. The area of ​​each bubble obtained is converted into a circle, and the diameter when converted into this circle is calculated, and the arithmetic mean of each of these values ​​is calculated. The bubbles present inside the cell walls are excluded from the measurement of the cell diameter. Also, bubbles whose cell walls are thought to have been chipped when the cross section of the test piece was prepared are also excluded from the measurement of the cell diameter. The detailed setting conditions for acquiring image data are as follows (monochrome conversion, smoothing filter (3x3, 8 neighbors, number of processes = 1), density unevenness correction (brighter than background, size = 5), NS method binarization (darker than background, clarity = 9, sensitivity = 1, noise removal, density range = 0 to 255), contraction (8 neighbors, number of processes = 1), image selection by feature (area) (only select 10000 to infinity μm2, 8 neighbors), expansion with no connection to adjacent areas (8 neighbors, number of processes = 3), measurement of each circle equivalent diameter (calculated from area, 8 neighbors)).

[0097] As shown in Table 1, Examples 1 to 5 were better in both adhesion rate and adhesion strength, and also had improved fire resistance, compared with Comparative Examples 1 to 4. In particular, by comparing Examples 1 to 3 with Examples 4 and 5, it was confirmed that the fire resistance was better when the molar ratio (Ca / (Al+Si)) was 0.01 or less.

[0098] In Comparative Example 1, the density of the geopolymer foam was too low, so the adhesive strength was reduced and the fire resistance was poor. On the other hand, in Comparative Example 2, the density of the geopolymer foam was too high, so the adhesion rate was reduced and the fire resistance was poor. In Comparative Example 3, although the same geopolymer foam as in Comparative Example 2 was used, the use of adhesive resulted in poor fire resistance. In Comparative Example 4, the fire resistance was poor because no geopolymer foam was used and an adhesive was used.

[0099] As can be understood from the above description, a laminate in which a metal body and a geopolymer foam are directly bonded, and the density of the geopolymer foam is 100 kg / m 3 More than 600kg / m 3 When the adhesion rate is 50% or more, good fire resistance is achieved.

Claims

1. A laminate in which a metal body and a geopolymer foam are bonded together; The density of the geopolymer foam is 100 kg / m 3 More than 600kg / m 3 is as follows: The area ratio of the metal body and the geopolymer foam in the part of the metal body where the geopolymer foam is laminated is 50% or more; Laminate.

2. 2. The laminate of claim 1, wherein the geopolymer foam comprises a reaction product of an aluminosilicate and an alkali metal silicate, and an aggregate.

3. 3. The laminate of claim 2, wherein the molar ratio of Ca element to the sum of Al element and Si element in the geopolymer foam is 0.4 or less.

4. A fire-resistant panel comprising a laminate according to any one of claims 1 to 3.

5. A method for producing a laminate of a geopolymer foam and a metal body, comprising: A foamable composition slurry containing an aluminosilicate, an alkali metal silicate, aggregate, water, and a foaming agent is introduced into a mold in which the metal body is disposed or into a mold in which the metal body constitutes at least a part of the mold surface, and then the foamable composition slurry is foamed to a density of 100 kg / m 3 More than 600kg / m 3 A method for manufacturing a laminate, comprising the steps of forming a geopolymer foam and adhering the metal body and the geopolymer foam.

Citation Information

Patent Citations

  • Light weight aerated concrete composite panel

    JP1985010041A

  • Heat-insulating fireproof panel

    JP2014134071A